Legal humanism in the representation of the subjects of law in Fabla salvaje y Escalas by César Vallejo: a century after its publication - Velazco Lévano, Nilton César (2023)
From a systematic, hermeneutic and comparative method of analysis, this study aims to identify the process of dehumanisation in Fabla salvaje y Escalas, by César Vallejo. The author, with a peculiar narrative and poetic lyric, inaugurates and exhibits his narrative vein in a critical, dramatic, oniric, enigmatic and ironic way, and at the same time alerts us to the dangers, challenges and hopes that save us from this decomposition in which the subjects of law are immersed. On the one hand, the stories approach the recesses of the Andean experience and cosmovision until they explode in absurdity; and, on the other, they delve into the cosmopolitanism that the city of Lima seductively offers, as if preparing the author for what was to come later in Europe. In this way, he configures a subject of law based on the juridical humanism that characterises the Vallejian universe. The centenary of the publication of the aforementioned works is a good occasion to highlight the validity of the author’s humanist and utopian message.